A two-sample bidirectional Mendelian randomization analysis investigates associations between gut microbiota and type 2 diabetes mellitus - Song, Siyuan; Zhang, Qiling; Zhang, Li; Zhou, Xiqiao; Yu, Jiangyi (Frontiers in Endocrinology, 2024)
This study sought to elucidate the causal association between gut microbiota (GM) composition and type 2 diabetes mellitus (T2DM) through a comprehensive two-sample bidirectional Mendelian randomization analysis.